Extensive Circumferential Heterotopic Ossification Discovered at the Base of a Loop Ileostomy. (2nd December 2019) - Bosaily, Ahmad; Edminister, John; Magal, Samarchitha; Jamil, Mohammad; Lynn, Amy; Hall, Glenn
Abstract : Heterotopic ossification is a rare phenomenon defined by the formation of bone within nonossifying soft tissues. A rare variant of heterotopic ossification is heterotopic mesenteric ossification (HMO), in which there is involvement of the mesentery and surrounding intra-abdominal structures. There are only four previously reported cases of HMO involving an ileostomy. We present a case of HMO affecting an ileostomy which was discovered during elective stoma reversal in a 52-year-old male who required fecal diversion following perineal necrotizing fasciitis.